2005
DOI: 10.1111/j.1365-2575.2005.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of e‐government services: citizen trust, innovation and acceptance factors*

Abstract: Electronic government, or e-government, increases the convenience and accessibility of government services and information to citizens. Despite the benefits of e-government -increased government accountability to citizens, greater public access to information and a more efficient, cost-effective government -the success and acceptance of e-government initiatives, such as online voting and licence renewal, are contingent upon citizens' willingness to adopt this innovation. In order to develop 'citizen-centred' e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
1,354
5
58

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,659 publications
(1,477 citation statements)
references
References 32 publications
60
1,354
5
58
Order By: Relevance
“…Five studies [20,24,29,52,58] used TAM and TPB together, four of them [6,24,48,77] used even three theories or models, whereas three [32,68,74] Survey: [6], [8], [9], [12], [16], [20], [24], [29], [32], [48], [49], [52], [58], [63], [67], [68], [74], [77], [76], [79], [86]; Interview: [84], [86], [89]; Secondary Data Analysis: [31]; Case Study: [69] Information System Success Model (DeLone and McLean, 1992McLean, , 2003 Survey: [19], [22], [30], [32], [55], [59], [65], [68], [74], …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies [20,24,29,52,58] used TAM and TPB together, four of them [6,24,48,77] used even three theories or models, whereas three [32,68,74] Survey: [6], [8], [9], [12], [16], [20], [24], [29], [32], [48], [49], [52], [58], [63], [67], [68], [74], [77], [76], [79], [86]; Interview: [84], [86], [89]; Secondary Data Analysis: [31]; Case Study: [69] Information System Success Model (DeLone and McLean, 1992McLean, , 2003 Survey: [19], [22], [30], [32], [55], [59], [65], [68], [74], …”
Section: Resultsmentioning
confidence: 99%
“…The 'complexity' construct from DOI is similar to the perceived ease of use (PEOU) construct from TAM. Similarly, some researchers have suggested that perceived usefulness and relative advantage are the similar constructs [6]. Carter and Belanger [6] argued that they included both DOI and TAM in the e-government adoption because DOI adds up significant contribution to the prophecy of adoption intent [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-government is a popular field of research within IS without a commonly agreed upon definition but broadly understood as "the use of information technology to enable and improve the efficiency with which government services are provided to citizens, employees, businesses and agencies" [13]. In striving for the perceived benefits of e-government almost all governments around the world are enthusiastically embracing, or having e-government pressed upon them.…”
Section: E-governmentmentioning
confidence: 99%
“…Moreover, previous research has shown that voters might prefer electronic voting systems over traditional paper-based methods even though the former might not perform better than the latter in terms of efficiency or effectiveness, and could be potentially more vulnerable [14], [19]. 4 More generally, the information systems literature has recognized that, in order to be successfully adopted and trusted, technology-based transactions must be perceived as useful, easy to use and secure [11], [13]. Neglecting these issues when considering the introduction of electronic voting systems might result in technology becoming a barrier, rather than a tool for increasing citizens' participation and trust in elections, with potentially undesirable and dangerous implications for the perceived legitimacy of the democratic process [18], [26], [28].…”
Section: Introductionmentioning
confidence: 99%